Effect Of Floating Plant Growth Rate On Water Quality Performance Of Wetland In Treating Domestic Sewage - Shamsudin, Nur Dhaniah Athirah (Universiti Sains Malaysia, 2022)
A man-made system that mimics the function and structures of natural wetland are called constructed wetlands. It has the ability to treat sewage water with low technology, low energy requirements, affordable and easy to maintain. However, how it works in tropical climates is still unknown and there is a need to figure out the sustainability of floating plants in treating domestic sewage. This study sought to achieve three main objectives that are first, to compare the pollutant removal efficiency of floating plants in treating domestic sewage, to investigate the growth rate of selected floating plants in domestic sewage treatment and to recommend the best plant for use in floating plant constructed wetland. The data was collected through a pilot constructed wetland in USM, Engineering Campus that is integrated with two species of floating plants which is Water Hyacinth and Water Lettuce. The parameters studied were chemical oxygen demand (COD), total suspended solids (TSS), and ammoniacal nitrogen (AN). The findings reveal that the removal efficiency of Water Hyacinth is higher for all COD (40.96%), TSS (43.94%), and NH3-N (24.35%) compare to Water Lettuce with COD (26.86%) TSS (17.79%), and NH3-N (15.55%). Even Water Hyacinth has a lower growth rate than Water Lettuce but they have higher biomass to uptake nutrients with just a small increment of area coverage. Therefore, Water Hyacinth is more reasonable to implement in floating plant constructed wetland as it needed less maintenance than Water Lettuce to achieve standard A for TSS and COD and standard B for NH3-N based on Malaysia Wastewater Effluent Discharge Standards.